2021
DOI: 10.1177/00207640211068977
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ experiences and perspectives of factors associated with relapse in Iranian people living with schizophrenia: A qualitative study

Abstract: Background: Relapse in People Living with Schizophrenia (PLS) has several reasons and recognizing these can increase the effectiveness of treatment interventions. Formal and informal caregivers are an informed source to reduce relapse in PLS. Aim: This study explores the caregivers’ perspective in Iran on the factors affecting relapse in PLS. Method: A total of 28 caregivers (16 formal caregivers and 12 informal caregivers) of PLS were enrolled in our qualitative study. A content analysis was conducted using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…The mental health system in Iran is limited to psychiatric hospitals and psychiatric beds in general hospitals. In the last decade, projects such as the integration of the mental health system in primary health care, the establishment of comprehensive mental health centers in metropolitan areas, and the provision of home visit services and follow-up after discharge have been implemented in a limited and regional manner, but they did not expand due to a lack of structural and budgetary support [ 31 , 32 ]. People with psychiatric disorders are now forgotten after discharge from the hospital until the next relapse occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mental health system in Iran is limited to psychiatric hospitals and psychiatric beds in general hospitals. In the last decade, projects such as the integration of the mental health system in primary health care, the establishment of comprehensive mental health centers in metropolitan areas, and the provision of home visit services and follow-up after discharge have been implemented in a limited and regional manner, but they did not expand due to a lack of structural and budgetary support [ 31 , 32 ]. People with psychiatric disorders are now forgotten after discharge from the hospital until the next relapse occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that seems to be effective in MHSR is insurance coverage. Although in the last decade, the Iranian Ministry of Health and Medical Education has tried to provide primary insurance coverage to the public through Iranian Health Insurance, insurance coverage for mental health services does not meet the needs of patients [ 32 , 35 ]. Various insurances cover between 90 and 97% of the costs of hospitalization in a public psychiatric hospital, but only cover 56 days of hospitalization per year and do not cover other psychiatric services such as monthly visits, medications, and rehabilitation services [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, a model should be designed to consider how risk factors affect relapse and the intervention should be based on reducing risk factors and strengthening protective factors. Previous studies have suggested the factors influencing relapse in different ecological layers (Ahmad et al, 2017; Izon et al, 2018; Kazadi et al, 2008; San et al, 2013; Xiao et al, 2015; Zabihi Poursaadati et al, 2021; Zhou et al, 2017). Risk factors for relapse include poor communication skills (Wu et al, 2017), cognitive deficits (Trapp et al, 2013), negative attitudes toward illness and treatment (Moritz et al, 2014), high expressed emotion in the family (Izon et al, 2018; Maarefvand et al, 2017), lack of effective and trained caregivers (Gurak & Weisman de Mamani, 2016), negative family attitudes toward the illness and treatment (Brain et al, 2018; Zabihi Poursaadati et al, 2021), social exclusion (Reddy et al, 2019), stigma (Corrigan et al, 2012; Couture & Penn, 2003; Price et al, 2016), poor insurance coverage (Fortney et al, 2009; Mansouri et al, 2013; Price et al, 2016), lack of access to professional care (Keynejad et al, 2018; Lund et al, 2012), and weak policies in mental health (Abdulmalik et al, 2013; Rebello et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While interpreting the findings of this study some limitations have to be kept in mind. First, the results of our study are constrained due to all limitations inherent to qualitative study designs (Maarefvand et al, 2017; Zabihi Poursaadati et al, 2021). Second, our study did not include community members and family members of PLS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation